Genome analysis and physiological comparison of Alicycliphilus denitrificans strains BC and K601(T.). - Margreet J Oosterkamp (Public Library of Science (PLoS), 2013)
The genomes of the Betaproteobacteria Alicycliphilus denitrificans strains BC and K601(T) have been sequenced to get insight into the physiology of the two strains. Strain BC degrades benzene with chlorate as electron acceptor. The cyclohexanol-degrading denitrifying strain K601(T) is not able to use chlorate as electron acceptor, while strain BC cannot degrade cyclohexanol. The 16S rRNA sequences of strains BC and K601(T) are identical and the fatty acid methyl ester patterns of the strains are similar. Basic Local Alignment Search Tool (BLAST) analysis of predicted open reading frames of both strains showed most hits with Acidovorax sp. JS42, a bacterium that degrades nitro-aromatics. The genomes include strain-specific plasmids (pAlide201 in strain K601(T) and pAlide01 and pAlide02 in strain BC). Key genes of chlorate reduction in strain BC were located on a 120 kb megaplasmid (pAlide01), which was absent in strain K601(T). Genes involved in cyclohexanol degradation were only found in strain K601(T). Benzene and toluene are degraded via oxygenase-mediated pathways in both strains. Genes involved in the meta-cleavage pathway of catechol are present in the genomes of both strains. Strain BC also contains all genes of the ortho-cleavage pathway. The large number of mono- and dioxygenase genes in the genomes suggests that the two strains have a broader substrate range than known thus far.